Is maternal negative affectivity related to psychosocial behavior of preterm and term-born toddlers through mother–child interaction? - Krijnen, L. J. G.; Verhoeven, M.; van Baar, A. L. (Frontiers in Psychology, 2022)
Introduction: Children born moderately to late preterm (MLP) are more prone to psychosocial difficulties than their term-born counterparts. Maternal negative affectivity (NA) - a relatively stable personality trait characterized by the tendency to experience negative thoughts, feelings and emotions - has been related to more psychosocial problems in their offspring, and to a lower quality of mother-child interactions. As MLP children seem more sensitive to their early caregiving environment, they might be more affected by maternal NA and interaction style than their term-born peers. The current study investigated whether maternal NA predicted child’s psychosocial outcomes through quality of mother-child interaction, and if these associations differed between MLP and term-born children. Methods: The sample consisted of 108 MLP and 92 term-born children and their mothers. At 18 months corrected age, maternal NA was measured using a self-report questionnaire and mother-child interaction was observed during two structured tasks. Five subscales of mother-child interaction were assessed: negative interaction, reciprocal engagement, emotional support, maternal stimulation and mother-led interaction. At 24 months corrected age, social-emotional difficulties, internalizing and externalizing problems were assessed using mother-report. Results: For MLP children, maternal NA directly, positively, predicted social-emotional difficulties (b = 0.57) and internalizing problems (b = 0.45), but no mediation effect of mother-child interaction was found. For term-born children, no direct effect but a mediation effect of mother-led interaction was found: Higher levels of maternal NA predicted less mother-led interaction which in turn predicted more problems. Birth status did not moderate any of the relationships, showing that the differences in patterns of effects found within the MLP and term-born group did not reach statistical significance. Discussion: Maternal NA was found to be a risk factor for psychosocial outcomes in toddlers, either directly for MLP children or indirectly through mother-led interaction for term-born children. These findings suggest that the process through which maternal NA affects psychosocial outcomes may be different for MLP and term-born children. However, as the examined moderation effects of birth status did not reach statistical significance, more research using larger sample sizes is needed to study mother-child interaction in greater detail.